Type of underwear worn and markers of testicular function among men attending a fertility center. Issue 9 (8th August 2018) - Mínguez-Alarcón, Lidia; Gaskins, Audrey J; Chiu, Yu-Han; Messerlian, Carmen; Williams, Paige L; Ford, Jennifer B; Souter, Irene; Hauser, Russ; Chavarro, Jorge E
Abstract: STUDY QUESTION: Is self-reported type of underwear worn associated with markers of testicular function among men at a fertility center? SUMMARY ANSWER: Men who reported most frequently wearing boxers had higher sperm concentration and total count, and lower FSH levels, compared to men who did not. WHAT IS KNOWN ALREADY: Elevated scrotal temperatures are known to adversely affect testicular function. However, the epidemiologic literature on type of underwear, as a proxy of scrotal temperature, and male testicular function is inconsistent. STUDY DESIGN, SIZE, DURATION: This is a cross-sectional study including 656 male partners of couples seeking infertility treatment at a fertility center (2000–2017). PARTICIPANTS/MATERIALS, SETTING, METHODS: Self-reported information on type of underwear worn was collected from a take-home questionnaire. Semen samples were analyzed following World Health Organization guidelines. Enzyme immunoassays were used to assess reproductive hormone levels and neutral comet assays for sperm DNA damage. We fit linear regression models to evaluate the association between underwear type and testicular function, adjusting for covariates and accounting for multiple semen samples. MAIN RESULTS AND THE ROLE OF CHANCE: Men had a median (interquartile range) age of 35.5 (32.0, 39.3) years and BMI of 26.3 (24.4, 29.9) kg/m 2 . About half of the men (53%; n = 345) reported usually wearing boxers. Men who reported primarily wearing boxers had a 25% higher sperm concentration (95% CI = 7, 31%), 17% higher total count (95% CI = 0, 28%) and 14% lower serum FSH levels (95% CI = −27, −1%) than men who reported not primarily wearing boxers. Sperm concentration and total count were inversely related to serum FSH. Furthermore, the differences in sperm concentration and total count according to type of underwear were attenuated after adjustment for serum FSH. No associations with other measured reproductive outcomes were observed. LIMITATIONS, REASONS FOR CAUTION: Our results may not be generalizable to men from the general population. Underwear use was self-reported in a questionnaire and there may be misclassification of the exposure. The cross-sectional design limits causal inference, and residual confounding is still possible owing to lack of information on other modifiable life styles that can also modify scrotal heat (e.g. type of trousers worn, textile fabric of the underwear). Blood sampling was not limited to the morning and, as a result, we may have missed associations with testosterone or other hormones with significant circadian variation despite statistical adjustment for time of blood draw. WIDER IMPLICATIONS OF THE FINDINGS: Certain styles of male underwear may impair spermatogenesis and this may result in a compensatory increase in gonadotrophin secretion, as reflected by higher serum FSH levels among men who reported most frequently wearing tight underwear. Confirmation of these findings, and in particular the findings on FSH levels suggesting a compensatory mechanism, is warranted. STUDY FUNDING/COMPETING INTEREST(S): The project was financed by Grants (R01ES022955, R01ES009718, P30ES000002, and K99ES026648) from the National Institutes of Health. None of the authors has any conflicts of interest to declare.